Is China Over-Investing and Does it Matter? - Lee, Il (IMF Working Papers; Working Paper, 2012)
Now close to 50 percent of GDP, this paper assesses the appropriateness of China's current investment levels. It finds that China's capital-to-output ratio is within the range of other emerging markets, but its economic growth rates stand out, partly due to a surge in investment over the last decade. Moreover, its investment is significantly higher than suggested by cross-country panel estimation. This deviation has been accumulating over the last decade, and at nearly 10 percent of GDP is now larger and more persistent than experienced by other Asian economies leading up to the Asian crisis. However, because its investment is predominantly financed by domestic savings, a crisis appears unlikely when assessed against dependency on external funding. But this does not mean that the cost is absent. Rather, it is distributed to other sectors of the economy through a hidden transfer of resources, estimated at an average of 4 percent of GDP per year.